Awe Narratives: A Mindfulness Practice to Enhance Resilience and Wellbeing - Thompson, Jeff (Frontiers in Psychology, 2022)
It is necessary to have available a variety of evidence-based resilience practices as we experience life’s stressors including the on-going COVID-19 pandemic. Evoking, experiencing, and reflecting on awe moments by developing and sharing an “awe narrative” is a type of mindfulness technique that can have the potential to help someone flourish, enhance their resilience, and have a positive impact on their overall wellbeing. This paper explores how constructing an awe narrative can assist the individual while also possibly having a positive impact on others.